2013
DOI: 10.3758/s13423-013-0536-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual context modulates potentiation of grasp types during semantic object categorization

Abstract: Substantial evidence suggests that conceptual processing of manipulable objects is associated with potentiation of action. Such data have been viewed as evidence that objects are recognized via access to action features. Many objects, however, are associated with multiple actions. For example, a kitchen timer may be clenched with a power grip to move it, but pinched with a precision grip to use it. The present study tested the hypothesis that action evocation during conceptual object processing is responsive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 39 publications
1
41
1
Order By: Relevance
“…Future EEG studies should assess whether markers of motor recruitment during object perception (e.g., Mu rhythm modulation) show residual activation of functional gestures, dissociated from structural gestures, when objects are presented in extrapersonal space. Regardless, the present finding indicates the visual context in which objects appear is an important modulating factor of affordance evocation (Costantini et al, 2010;Kalénine et al, 2014), but also competition.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Future EEG studies should assess whether markers of motor recruitment during object perception (e.g., Mu rhythm modulation) show residual activation of functional gestures, dissociated from structural gestures, when objects are presented in extrapersonal space. Regardless, the present finding indicates the visual context in which objects appear is an important modulating factor of affordance evocation (Costantini et al, 2010;Kalénine et al, 2014), but also competition.…”
Section: Discussionmentioning
confidence: 44%
“…Moreover, the relative importance of structural and functional gesture activation depends on visual context and action goals. For instance, Kalénine, Shapiro, Flumini, Borghi, and Buxbaum (2014) showed that semantic categorization of conflictual objects entailed stimulus-response compatibility effects with the functional gesture when the object was presented in a use context (e.g., calculator on desktop), but with the structural gesture when the object was presented in a move context (e.g., calculator in drawer). Yet the existence of conflict effects between functional and structural affordances during object perception has never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is evidence that the immediate visual context can affect conceptual retrieval: If an object is depicted in a context consistent with its use (e.g., a kitchen timer on the counter next to a pot of food bubbling on the stove), the action associated with using the object is more readily available than when the same object is depicted in a context consistent with picking it up (e.g., when the timer is in a kitchen drawer; Kalénine, Shapiro, Flumini, Borghi, & Buxbaum, 2014) 2 . There is also neural evidence that surrounding objects can influence conceptual activation.…”
Section: (3) the Concurrent Context Or On-going Goals (Ie Task)mentioning
confidence: 99%
“…Moreover, the tool manipulation knowledge that is activated at any given time are in part a function of context. “Context” may include task demands and intentions, recent actions performed, and expected forthcoming actions (e.g., Borghi, 2014; Kalenine, Shapiro, Flumini, Borghi, & Buxbaum, 2014; Lee, Middleton, Mirman, Kalenine, & Buxbaum, 2013). For example, when one encounters a tool in the array, absent of the explicit intention to use it, activation of manipulation knowledge is influenced by other “bottom up” information, including episodic memories of what we have done before, other recently-performed actions that may still be activated (i.e., manipulation knowledge for other recently encountered objects), and affordances (Jax & Buxbaum, 2010).…”
Section: Additional Assumptions Of the 2as+ Theoretical Modelmentioning
confidence: 99%
“…For example, visual (and to a lesser degree, tactile and auditory) input provides us with numerous action choices (Botvinick et al, 2009; Cisek, 2007; Cisek & Kalaska, 2010; Pavese & Buxbaum, 2002; Schubotz, Wurm, Wittmann, & von Cramon, 2014); information about upcoming and recently performed task steps result in lingering and anticipatory activations of actions that may (or may not) be relevant in the present (Cooper & Schallice, 1997; Cooper & Shallice, 2000; Schwartz, 1995). Moreover, even single objects may be compatible with numerous actions, which are frequently co-activated (Jax & Buxbaum, 2013; Jax & Buxbaum, 2010; Kalenine et al, 2014; Watson & Buxbaum, 2015). Skilled tool use requires a mechanism for rapid and flexible selection of task-relevant actions.…”
Section: Additional Assumptions Of the 2as+ Theoretical Modelmentioning
confidence: 99%